A call to combat the burden of Allergic Contact Dermatitis among children and adolescents with type 1 diabetes mellitus using medical adhesives: a cross-sectional observational study - Alsuwaidi, Laila; Kanj, Lana; Rowaiaee, Rasha; Kanj, Sara; Otaki, Farah; Otypi, Wafa; Bejjani, Mireille (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundThe increasing prevalence of Type 1 Diabetes Mellitus (T1D) has led to the development of advanced technologies such as Continuous Glucose Monitors (CGMs) and insulin infusion pumps. These devices rely on adhesives to attached to the skin, which can trigger Allergic Contact Dermatitis (ACD) in some individuals. Despite their growing use, data on ACD prevalence among children/adolescents with T1D using adhesive-based medical devices in the United Arab Emirates (UAE) and the Gulf Cooperation Council (GCC) region remains limited. This study aimed to assess the prevalence of ACD in children/adolescents with T1D using CGMs in the UAE, and evaluate the association between device use and ACD. It also explored trends in immune-related comorbidities that could impact glycemic control.MethodsA cross-sectional observational study was conducted in collaboration with Dubai Diabetes Center (DDC). Medical records of 232 children/adolescents with T1D, receiving care at DDC between January 2020 and January 2023, were analyzed. Descriptive statistics were used to calculate proportions, and ACD prevalence was determined with a 95% Confidence Interval (CI) using Poisson distribution. Fisher’s exact test was applied to explore associations between categorical variables.ResultsAmong 232 study individuals, 87% (202 out of 232 individuals) used smart medical devices for glucose monitoring. Of these, 16 had a documented history of ACD, indicating a prevalence rate of 7.92% (95% CI: 4.6, 12.54). No statistically significant association was found between smart devices use and ACD development (p-value = 0.581). ACD prevalence was higher among females using adhesives (9.37%) compared to their male counterparts (6.6%).ConclusionThis study aligns with United Nations’ Sustainable Development Goals 3 and 4 by highlighting ACD prevalence among children/adolescents with T1D using CGMs in the UAE. It underscores the need for biomedical manufacturers to disclose adhesive chemical compositions to facilitate the development of safer alternatives. Additionally, healthcare professionals should be educated on dermatological risks associated with adhesive-based devices, enabling them to provide more comprehensive care and improve individual outcomes.